A commonwealth of knowledge : science, sensibility, and white South Africa, 1820-2000 - Dubow, Saul (OUP E-Books., 2006)
This is the first full study of the relationship of knowledge to national identity formation in modern South Africa. It explores how the cultivation of knowledge served to support white political ascendancy and claims to nationhood. Elegantly written and wide ranging, the book addresses major themes in both South African and comparative imperial historiography. - ;A Commonwealth of Knowledge addresses the relationship between social and scientific thought, colonial identity, and political power in nineteenth- and twentieth-century South Africa. It hinges on the tension between colonial knowled.